2021
DOI: 10.21037/tau-20-989
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model containing PI-RADS v2 score for postoperative seminal vesicle invasion among prostate cancer patients

Abstract: Background: Seminal vesicle invasion (SVI) is considered to be one of most adverse prognostic findings in prostate cancer, affecting the biochemical progression-free survival and disease-specific survival. Multiparametric magnetic resonance imaging (mpMRI) has shown excellent specificity in diagnosis of SVI, but with poor sensitivity. The aim of this study is to create a model that includes the Prostate Imaging Reporting and Data System version 2 (PI-RADS v2) score to predict postoperative SVI in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…ECE and SVI are two crucial pathologic features of PCa, which have a significant impact on patient prognosis and surgical strategy [35]. The incidence of ECE and SVI appeared to be heterogeneous, with recent studies reporting rates ranging from 17% to 54% for ECE [6,7,36] and 8% to 17.6% for SVI [37][38][39]. In our study cohort, the incidence of ECE and SVI was found to be 46.8% and 17.4%, respectively, which is consistent with these reported in recent research.…”
Section: Discussionmentioning
confidence: 99%
“…ECE and SVI are two crucial pathologic features of PCa, which have a significant impact on patient prognosis and surgical strategy [35]. The incidence of ECE and SVI appeared to be heterogeneous, with recent studies reporting rates ranging from 17% to 54% for ECE [6,7,36] and 8% to 17.6% for SVI [37][38][39]. In our study cohort, the incidence of ECE and SVI was found to be 46.8% and 17.4%, respectively, which is consistent with these reported in recent research.…”
Section: Discussionmentioning
confidence: 99%